Fragmentation of 400 A MeV carbon ions on Cu target. (July 2019) - Zhang, Dong-Hai; Gou, Chen-Wei; Li, Jun-Sheng; Li, Wei; Wu, Guo-Feng; Yao, Dong; Kodaira, S.
Abstract: The total charge-changing cross-section and the partial cross-section of projectile fragments (PFs) production for the fragmentation of 12 C on Cu target at the highest energy close to about 400 A MeV is investigated. It is found that the total charge-changing cross-sections of PFs production is independent of the beam energy, but the partial cross-sections of PFs production increase with decrease beam energy for the same target. The total charge-changing reaction cross section is in agreement with the prediction of Bradt-Peters semi-empirical formula, PHITS and NUCFRG2 models. The partial cross section of PFs production is larger than the prediction of PHITS model. The average scattering angle of beam particle is smaller than the mean emission angle of PF, and the width of scattering angle distribution of beam particle is smaller than that of emission angle distribution of PF. Highlights: Dependence of the total chare-changing cross-section and the partial cross-section on beam energy are investigated. The mean scattering angle of beam particles and mean emission angle of projectile fragments are presented. The scattering angle distribution of beam particles and emission angle distribution of fragments are presented. The results are helpful not only in understanding the fragmentation mechanism of carbon nuclei but also radiation therapy.